Isolation and characterization of bacteriophage infecting Lactobacillus plantarum KCCM 12116 - Jiyoung Oh; Jong-Hyun Park (한국식품과학회지, 2021)
Bacteriophages (phages) are known determinants of kimchi microbial ecology. Lactobacillus plantarum is related to kimchi over-acidification during the late stages of kimchi fermentation. A phage infecting Lac. plantarum was isolated from kimchi and characterized. The phage population for kimchi in a market was 2.3 log particles/mL, which corresponded to 32% of the bacterial population on a log scale. The isolated phage was designated as ΦLP12116. ΦLP12116 which belonged to the Siphoviridae family and has a very narrow host range, infecting only Lac. plantarum. The phage was stable at a lactic acid concentration of 1.0% and pH 4.0 at 4oC, indicating that it could survive in kimchi. In the kimchi extract broth treated by the phage, the growth of Lac. plantarum KCCM 12116 was inhibited by 2.2 log CFU/mL compared to the growth in nonphage- treated broth. Therefore, this study suggests that the growth of Lac. plantarum, which is known as an acid-producing strain during late fermentation in kimchi, may be controlled using the phage. KCI Citation Count: 1